Employee Value Proposition, Exchange Ideology, and Intention to Stay : A Conceptual Analysis - Rounak, Sujata; Misra, Rajnish Kumar (Prabandhan: Indian Journal of Management, 2022)
The purpose of this paper was to analyze the preference for EVP attributes from the exchange ideology perspective of an individual, which would, in turn, impact an individual’s intention to stay in an organization. The study extensively reviewed literature and offered a conceptual framework to explain employees’ EVP attributes preference based on their exchange ideology orientation and its impacts on their intention to stay. A literature review established that compensation and career growth are preferred by individuals having a higher exchange ideology which would, in turn, lower their intention to stay. On the other hand, attributes such as training and development, work-life balance, and work environment are preferred by individuals with low exchange ideology, which positively impacts their intention to stay. To establish the validity of the conceptual framework as well as the observations, empirical research on the proposed propositions is required. The study’s implications involved understanding the EVP attributes from employee retention and organizational context. There is a paucity of research on the issue with minimal effort to analyze the relation involving the exchange ideology of individuals and the attributes preferred by them as offered by their employers.